Antibiotic Effect on Pseudomonas Aeruginosa Isolated From Patient In Hila City (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study, a total of 400 clinical samples were collected from patients different hospitals in hillacity((13.51%) Margin teaching hospital, (27.03%)Al-Hilla teaching hospital,( 43.24%) Babylon hospital formaternity and pediatric and (16.22%)Chest Disease Center) , ( 37 ) isolates were identified as to P. aeroginosa,from 9 (18%) isolates from burn specimen, 7 (14%) isolates from otitis , 5 (10%)isolates from UTI , 4 (8%)isolates from wound , 3(7.5%) was isolated from blood specimen where as 6 (6%)was isolated sputum andonly 3 (5%)isolates were detected from skin. The period of collection was extended from January 2019 toJune 2019. Also antibiotic susceptibility were preformed using disk employed diffusion and agar utilizingdilution processes. Furthermore , the resistance of isolate to a variety of antibiotics has been investigated andfound that these isolate have been resistance to more than one antibiotic : 37(100%) resistance to Cloxacilin, 37(100%) to Amoxicillin /Clavulanic acid, 37(100%) to cefotaxime, 36(97%) to ceftizoxone, 34(92%)to Ceftazidime, 14(37%) to Levofloxacin, 18(49%) to Gentamicin, , 3(8%) to Norfloxacin and 1(3%) toAzetronam.